Studies towards a biomimetic synthesis of simonol A - Zaidi, Jaffer (2022)
Illicium-derived neolignan natural products are of interest due to their often potent medicinal properties, particularly in the promotion of neurite outgrowth. Herein, we report our efforts towards the synthesis of simonol A, a recently discovered sesqui-neolignan. Three synthetic routes were designed, each based on our proposed biosynthesis of this compound and taking into account our experience with this general class of natural products. The routes were executed with varying degrees of success, the most effective being the third, in which a key intermediate in the synthesis of simonol A was isolated. Preparation of a dibrominated species, followed by a microwave-assisted double Suzuki-Miyaura cross coupling and finally allylation of a free phenol, gave us this intermediate in 35% yield over three steps. Investigations into a possible [3,3] sigmatropic rearrangement of this molecule were then carried out, supported by some computational studies. The thermal energy barrier for our proposed Claisen rearrangement was calculated to be 45.7 kcal/mol, indicating that a Lewis acid catalyst would most likely be required in order to carry out this reaction in practice. In comparison, the proposed neutral oxy-Cope rearrangement was found to have a calculated energy barrier of 35.6 kcal/mol, while the anionic equivalent had a much lower barrier of 8.1 kcal/mol. This suggested that if a neutral oxy-Cope rearrangement were to occur in the biosynthesis of simonol A as proposed, then this would need to be an enzyme-mediated process.